CONCEPTUAL AMBUSH OF DIGITAL TRANSFORMATIONS IN THE SYSTEMS OF GOVERNMENT MANAGEMENT: WIKILEAKS TODAY - Denys Shabanov (Публічне управління та регіональний розвиток)
The article carries out a comprehensive study of the theoretical foundations of the digital transformation of public administration through the prism of its conceptual field and conceptual model. The content of such definitions as «informatisation», «digitalisation», «digitalisation» and «digital transformation» is systematised and disclosed, their evolution and interrelation in the context of development of the public administration theory is traced. The essence of the digital transformation of public administration as a multidimensional process, covering technological, managerial and social dimensions, is defined, and its key principles are substantiated: inclusiveness, transparency, adaptability. The main regularities of digital transformation are identified and characterised, in particular, the transition from fragmented automation to integrated management and the growing role of data in management decision-making. The key features of the digital transformation of public administration are identified: integrity, adaptability, transparency, proactivity and citizen orientation. The typology of mechanisms of digital transformation is described, which includes technological, organisational, regulatory, communication and educational mechanisms, and the peculiarities of their institutional and resource support are determined. A conceptual model of digital transformation of public administration is proposed, which integrates technological, organisational, social and legal aspects into a single architecture. The main drivers of digital transformation (technological innovations, citizens' expectations, international standards) and barriers (financial constraints, digital competence, regulatory instability) are identified. The indicators of the effectiveness of the digital transformation of public administration are systematised, covering both quantitative indicators (level of accessibility of services, speed of decision-making) and qualitative characteristics (citizen satisfaction, reduction of administrative burden).